Prevalence of Vitamin D deficiency among individuals with Fontan palliation: A systematic review and meta-analysis - Firyal Khansa; Chairul Ichwan; Muhammad Haneef Ghifari; Muhammad Brilliant Daffa; Farah Rizky Nadia; Putri Oktaviani Zulfa; Derren David Christian Homenta Rampengan; Amanda Yufika; Naufal Gusti; Muhammad Iqhrammullah (Annals of Pediatric Cardiology)
Background: Children with one functional ventricle might receive the Fontan procedure as palliative management to prolong their lives. However, the heart remains functionally univentricular, which may result in disrupted absorption of nutrients, including Vitamin D. Individuals with Fontan circulation have limited physical activity and sun exposure, which might further contribute to Vitamin D deficiency. Objective: This study aimed to estimate the prevalence of Vitamin D deficiency among individuals with Fontan circulation and analyze probable contributing factors to it through meta-regression analysis. Methods: A predetermined search strategy was applied on PubMed, Scopus, Scilit, Web of Science, Europe PMC, and Google Scholar to identify relevant literature as of July 2024. In general, studies reporting the prevalence or incidence of Vitamin D deficiency (<20 ng/mL) among Fontan patients were eligible for inclusion. Only cohort and cross-sectional studies were included. The pooled estimates were carried out using a restricted maximum-likelihood model and Freeman–Tukey double-arcsine transformation (FTT). Results: Six studies were included, comprising 255 individuals with the Fontan circulation. The prevalence of Vitamin D deficiency was 51% (95% confidence interval: 35%– 67%) with noticeable heterogeneity (I2 = 84.38%; p-Het <0.001). Extracardiac conduit/lateral tunnel (P = 0.003) was the main contributor to the heterogeneity. Conclusion: Vitamin D deficiency is highly prevalent among individuals with Fontan palliation, highlighting the need for active monitoring and investigation into the benefits of Vitamin D supplementation. PROSPERO registration: CRD42024574724.